Prominent longitudinal strain reduction of left ventricular basal segments in treatment-naïve Anderson-Fabry disease patients. (6th August 2018) - Esposito, Roberta; Galderisi, Maurizio; Santoro, Ciro; Imbriaco, Massimo; Riccio, Eleonora; Maria Pellegrino, Angela; Sorrentino, Regina; Lembo, Maria; Citro, Rodolfo; Angela Losi, Maria; Spinelli, Letizia; Trimarco, Bruno; et al.
Abstract: Aims: Little is known about regional longitudinal strain (LS) distribution in early stages of Anderson-Fabry disease (AFD) cardiomyopathy. We investigated regional left ventricular (LV) patterns of LS strain and base-to-apex behaviour of LS in treatment-naïve AFD patients. Methods and results: Twenty-three consecutive AFD patients at diagnosis and 23 healthy controls without cardiovascular risk factors and matched for age and sex to the patients, underwent a comprehensive evaluation of target organs. An echo-Doppler exam, including determination of regional and global LS strain (GLS) was obtained. The average LS of 6 basal (BLS), 6 middle (MLS), and 5 apical (ALS) segments and relative regional strain ratio [ALS/(BLS + MLS)] were also calculated. Ejection fraction and diastolic indices did not differ between the two groups. LV mass index was greater in AFD ( P < 0.01). GLS ( P = 0.006), BLS ( P < 0.0001), and MLS ( P = 0.003), but not ALS, were lower in AFD patients and relative regional strain ratio was higher in AFD ( P < 0.01) than in controls. These analyses were confirmed separately in the two genders and even after excluding patients with wall hypertrophy. By subdividing AFD patients according to lysoGB3 levels, 9 patients with lysoGB3 ≥ 1.8 ng/L had lower ALS compared to 11 patients with lysoGB3 < 1.8 ng/L ( P < 0.01). Conclusion: In naïve AFD patients, we observed an early reduction of LV LS, involving mainly LV basal myocardial segments. Nevertheless, the association found between the higher lysoGB3 levels and the lower apical cap LS demonstrates that apical segments LS, despite still normal, is not spared at diagnosis.